STRATEGI BADAN PENGAWAS PEMILU DALAM MENCEGAH POTENSI PELANGGARAN PEMASANGAN ALAT PERAGA KAMPANYE DI KABUPATEN LOMBOK TIMUR - Jumaah, Siti Hidayatul (Jurnal Ilmu Politik dan Pemerintahan, 2024)
Installation of Campaign Praga Equipment is an election stage where violations are often found, such as: installation locations that do not comply with regulations, and installation that is not according to schedule. This research aims to analyze the Election Supervisory Agency's strategy in preventing potential violations of APK installation in the 2024 simultaneous elections in East Lombok Regency. The research method used is a descriptive research method with a qualitative approach. Data collection techniques use interview techniques, observation and documentation studies. The data sources in this research consist of two, namely primary and secondary data. The data analysis technique uses three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the Election Supervisory Agency's strategy has worked quite well. This can be seen from several aspects, namely: first, the program aspect shows quite good results, where Bawaslu has developed several program strategies, namely: 1) identifying potential violations; 2) coordinate with the campaign team; 3) coordinate with Panwaslu; 4) submit a letter of appeal; 5) social media publications; and 6) On-site prevention. Second, the budget aspect shows poor results, considering that there is no official budget allocated specifically to prevent and overcome violations of the installation of campaign equipment. The budget still depends on the budget from the Provincial Bawaslu. Third, the procedural aspect shows quite good results, considering that there are clear regulations in supervising the installation of campaign praga equipment through Bawaslu Regulation Number 28 of 2018 concerning Supervision of General Election Campaigns.